FOREIGN EXPERIENCE OF IMPROVING TAX ADMINISTRATION (World Bulletin of Social Sciences, 2024)
This article is devoted to the investigation of international experience in improving tax administration and assesses their applicability to Uzbekistan. Moreover, the article examines theoretical foundations of efficient tax administration, analyzes examples of successful reforms in selected countries, as well as identifies opportunities for introducing this practice in Uzbekistan